2019
DOI: 10.21037/sci.2019.02.03
|View full text |Cite
|
Sign up to set email alerts
|

The past, present, and future of CRM1/XPO1 inhibitors

Abstract: Therapies targeted at inhibiting nucleo-cytoplasmic transport have found broad applications in the field of oncology. Chromosome region maintenance 1 (CRM1), better known as exportin 1 (XPO1), is the protein transporter responsible for the nucleo-cytoplasmic shuttling of most of the tumor suppressor proteins (TSP) and growth regulatory factors. XPO1 is also upregulated in many malignancies and associated with a poor prognosis. Its inhibition has been a target of therapy, and hence, the selective inhibitors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 64 publications
2
81
0
Order By: Relevance
“…This peptide was derived from the XPO1 (exportin-1/CRM1) protein, which is thought to function as the sole nuclear exporter for many different tumor suppressor and growth regulatory proteins including p53, p27, FOXO1, IkB, cyclin B1, cyclin D1 and survivin (38). XPO1 is overexpressed and associated with poor prognosis in multiple cancers including hematological malignancies and difficult to treat cancers such as pancreatic cancer and HCC (41,43,47). Inhibition of XPO1 is gaining traction as a cancer therapeutic target following clinical trials, and our data suggest it could also be a target for KIR2DS2based NK cell therapeutics (40).…”
Section: Discussionmentioning
confidence: 76%
“…This peptide was derived from the XPO1 (exportin-1/CRM1) protein, which is thought to function as the sole nuclear exporter for many different tumor suppressor and growth regulatory proteins including p53, p27, FOXO1, IkB, cyclin B1, cyclin D1 and survivin (38). XPO1 is overexpressed and associated with poor prognosis in multiple cancers including hematological malignancies and difficult to treat cancers such as pancreatic cancer and HCC (41,43,47). Inhibition of XPO1 is gaining traction as a cancer therapeutic target following clinical trials, and our data suggest it could also be a target for KIR2DS2based NK cell therapeutics (40).…”
Section: Discussionmentioning
confidence: 76%
“…Taking all these findings together, we postulate that Xpo7 is a regulator of the Hh pathway that cooperates with SuFu in excluding Gli2/3 from the nucleus and facilitating the maintenance of the "OFF" state for Hh signaling in the absence of ligand. Given that drugs targeting nuclear export pathways have recently found their way to the clinic (40), our data may be the stepping stone towards designing novel therapeutics against Gli-dependent tumors. (16).…”
Section: Disscussionmentioning
confidence: 99%
“…CAPE targets specifically a non-catalytic cysteine 528 of XPO1/ CRM1, which results in inhibition of its function. (Wang and Liu 2019). Among the target proteins of XPO1/CRM1 are NF-κB, Wnt/β-catenin, PI3K/Akt, p53, FOXOs (Forkhead box proteins), etc.…”
Section: Signal Transduction Modulationmentioning
confidence: 99%
“…Among the target proteins of XPO1/CRM1 are NF-κB, Wnt/β-catenin, PI3K/Akt, p53, FOXOs (Forkhead box proteins), etc. (Wang and Liu 2019). It has been reported that XPO1/CRM1 inhibitors are among the anticancer agents with the broadest spectrum of activity towards diverse malignancies (Wang and Liu 2019).…”
Section: Signal Transduction Modulationmentioning
confidence: 99%
See 1 more Smart Citation